Democratic Parenting and Emotional Intelligence: A Study on Teenagers from Divorced Families - Sahureka, Princess Agracia Miltha; Soetjiningsih, Christiana Hari (Jurnal Bimbingan dan Konseling Terapan, 2023)
This study explores the relationship between the democratic parenting style and emotional intelligence in teenagers whose parents are divorced, focusing on a specific population in the Wainitu region of Ambon City, Maluku. Utilizing a Pearson's product-moment correlation, the research findings indicate a significant positive correlation between democratic parenting and emotional intelligence with a correlation coefficient of 0.314 (p < 0.05). The data suggests that effective democratic parenting contributes to approximately 9.85% of the quality of emotional intelligence among these teenagers. The study concludes that while other factors can impact emotional intelligence, a democratic parenting style is a vital contributing element, underscoring the importance of the family as the primary context for character formation. However, the study also acknowledges the complexities of emotional development in children from divorced families, emphasizing the need for further research in this area, including exploration of other parenting styles. The results provide valuable insights for families, educators, and policymakers in supporting emotional intelligence development in teenagers from divorced families.